2015
DOI: 10.1167/iovs.15-16577
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Risk Factors for Early-Onset Myopia in Young Asian Children

Abstract: Genetic factors may have a greater contribution to early development of refractive error compared to environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
98
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 36 publications
(57 reference statements)
3
98
1
3
Order By: Relevance
“…), children aged 3 years (Chua et al. ), adults aged 18–24 years (Lee et al. ) and adults aged 50 years or older (Pan et al.…”
Section: Resultsmentioning
confidence: 99%
“…), children aged 3 years (Chua et al. ), adults aged 18–24 years (Lee et al. ) and adults aged 50 years or older (Pan et al.…”
Section: Resultsmentioning
confidence: 99%
“…In 7681 children aged 5–16 years old, myopia (adjusted OR = 1.17, 95% CI 1.03–1.32; p = 0.015) and high myopia prevalence (adjusted OR = 2.31, 95% CI 1.17–4.57; p = 0.016) were associated with computer use . However, in 572 children aged 3 years old the number of hours per day playing with handheld devices (adjusted OR = 1.04, 95% CI 0.67–1.61; p = 0.86) and using computers (adjusted OR = 0.92, 95% CI 0.31–2.74; p = 0.88) was not associated with myopia . At 3 years old only 6.1% of the children had myopia and exposure to digital devices might not be enough to cause myopia at this point in time.…”
Section: Resultsmentioning
confidence: 99%
“…'s study in Taiwan revealed that time spent using computers was associated with a longer AL ( p = 0.001) . In contrast, handheld devices and computers were not significantly associated with SER, AL or myopia in the Singapore Cohort Study of the Risk Factors for Myopia (SCORM) study …”
Section: Discussionmentioning
confidence: 98%